Ischemic postconditioning activates cardiac MMP-2 and decreases biglycan level as well as miR-34a-5p and miR-195-5p expression in early reperfusion in a porcine infarction model. (10th June 2022) - Szabados, T; Gomori, K; Ferdinandy, P; Gyongyosi, M; Gorbe, A; Bencsik, P
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Kooperatív Doktori Program Doktori Hallgatói Ösztöndíj (KDP-2020) Hungarian Scientific Research Fund-OTKA-138223 Background: Matrix metalloproteinase-2 (MMP-2) has been shown to be activated during myocardial ischemia-reperfusion (IR) injury leading to degradation of cardiac contractile proteins. In previous investigation, ischemic postconditioning (IPoC) failed to decrease myocardial necrosis in porcine model of acute myocardial infarction (AMI). However, IPoC significantly reduced the severity of myocardial microvascular obstruction (MVO) compared to ischemic control. Therefore, our aim was to reveal if two major extracellular players of cardiac pathophysiology, MMP-2 and biglycan (BGN) are involved in the MVO reducing effect of IPoC in a porcine AMI model. Methods: AMI was induced in female domestic pigs (25-35 kg) with balloon catheter occlusion of the left descending coronary artery for 90 min in ischemic control group. IPoC group underwent 6×30 s I/R after 90-min occlusion. At the end of the 3-hour or 3-day reperfusion, infarcted left ventricular tissue samples were taken to determine MMP-2 activity and BGN levels as well as cardiac microRNA (miRNA) expression. Results: Cardiac MMP-2 activity showed significant increase in IPoC group as compared to ischemic control after 3h reperfusion but after 3d reperfusion no significant change was observed between the two groups. Cardiac BGN level in IPoC was significantly decreased as compared to ischemic control after 3h reperfusion, which difference was also abolished after 3d reperfusion due to the decrease of BGN level of ischemic control group. Ischemic postconditioning altered the expression of three miRNAs: miR-34a-5p, and miR-195-5p were downregulated, and miR-15b-5p was upregulated as compared to ischemic control. Conclusions: IPoC decreased MVO and BGN level and increased MMP-2 activity in the infarcted left ventricle during early reperfusion, and altered the expression on 3 cardiac miRNAs. Further increase was found in MMP activities after 3 days in both groups, which affected BGN level only in ischemic control group. Altered expression of miRNAs and early decrease in cardiac BGN level may contribute to the beneficial effect of IPoC on MVO.